Analisis Strategi Media Sosial Instagram dalam Meningkatkan Engagement Audiens pada Event Subfestival (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
This study aims to analyze the Instagram social media strategy implemented by Event Subfestival to enhance audience engagement based on the 4C Theory (Context, Communication, Collaboration, and Connection) proposed by Chris Heuer. This research employs a qualitative approach using a descriptive case study method. Data were collected through in-depth interviews, observations, and documentation of the management of the Event Subfestival Instagram account and were analyzed using the data analysis model developed by Miles, Huberman, and Saldaña. The findings reveal that Event Subfestival's Instagram social media strategy has effectively incorporated the four dimensions of the 4C Theory: Context, through the creation of relevant and engaging content; Communication, through active interaction with the audience; Collaboration, through partnerships with communities and media partners; and Connection, through efforts to establish and maintain long-term relationships with the audience. The implementation of these strategies has successfully increased audience engagement, strengthened the relationship between the event organizers and their audience, and supported the overall effectiveness of Event Subfestival's promotional activities.